Konstruksi Media Terhadap Isu Pinjam Online Dalam Perspektif Islam - Den Ajeng Khuluqiyah; Hanita Oktaviana; Hasna Fauziah Zaelani; Putri Rahmatika; Sulistiani Dewi; Hisny Fajrussalam (Universitas Islam Negeri Sumatera Utara, 2022)
The economy is everything that humans need to maintain the necessities of life. Along with the times where people are familiar with technology with online loans to meet their economic needs. Online loans are no longer foreign to the public, they can be done anywhere and anytime and the rise of online loan cases has a negative impact on society. Modern facilities that make it easy to borrow and borrow cause many problems in society. The popularity of online loans can be used by people for personal gain. In Islamic law, online loans are legal if the terms and conditions are carried out and based on an agreement. However, Islam also teaches that if you can, you should not need to make the loan.